Effect of polygenic load on striatal dopaminergic deterioration in Parkinson disease. (13th August 2019) - Lee, Myung Jun; Pak, Kyoungjune; Kim, Jong Hun; Kim, Yun Joong; Yoon, Jeehee; Lee, Jinwoo; Lyoo, Chul Hyoung; Park, Hyung Jun; Lee, Jae-Hyeok; Jung, Na-Yeon
Abstract : Objective: To investigate the effect of polygenic load on the progression of striatal dopaminergic dysfunction in patients with Parkinson disease (PD). Methods: Using data from 335 patients with PD in the Parkinson's Progression Markers Initiative (PPMI) database, we investigated the longitudinal association of PD-associated polygenic load with changes in striatal dopaminergic activity as measured by 123 I-N-3-fluoropropyl-2-β-carboxymethoxy-3β-(4-iodophenyl) nortropane ( 123 I-FP-CIT) SPECT over 4 years. PD-associated polygenic load was estimated by calculating weighted genetic risk scores (GRS) using 1) all available 27 PD-risk single nucleotide polymorphisms (SNPs) in the PPMI database (GRS1) and 2) 23 SNPs with minor allele frequency >0.05 (GRS2). Results: GRS1 and GRS2 were correlated with younger age at onset in patients with PD (GRS1, Spearman ρ = −0.128, p = 0.019; GRS2, Spearman ρ = −0.109, p = 0.047). Although GRS1 did not show an association with changes in striatal 123 I-FP-CIT availability, GRS2 was associated with a slower decline of striatal dopaminergic activity (interactions with disease duration in linear mixed model; caudate nucleus, estimate = 0.399, SE = 0.165, p = 0.028; putamen, estimate = 0.396, SE = 0.137, p = 0.016). Conclusions: Our results suggest that genetic factors for PD risk may have heterogeneous effects on striatal dopaminergic degeneration, and some factors may be associated with a slower decline of dopaminergic activity. Composition of PD progression–specific GRS may be useful in predicting disease progression in patients.